CLEVER-1 targeting antibody, bexmarilimab, supports HLA-DR expression and alters ex vivo responsiveness to azacitidine and venetoclax in myeloid malignancies - Aakko, Sofia; Ylitalo, Arno; Kuusanmäki, Heikki; Rannikko, Jenna H.; Björkman, Mari; Mandelin, Jami; Heckman, Caroline A.; Kontro, Mika; Hollmén, Maija (Springer Science and Business Media LLC, 2025)
Treatment of myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) requires new therapy options, especially for patients uneligible for intense chemotherapy or with relapsed or refractory disease. CLEVER-1 is a myeloid checkpoint protein, which can be targeted with a therapeutic function blocking antibody, bexmarilimab. Bexmarilimab has shown clinical efficacy in different solid tumors. Here, we show preclinical data demonstrating expression of CLEVER-1 on immature malignant myeloid cells and their derivates in MDS and AML bone marrow samples and AML cell lines. Highest CLEVER-1 levels were observed in AML with monocytic differentiation. Ex vivo treatment of AML/MDS bone marrow samples with bexmarilimab led to an increase in antigen-presenting human leukocyte antigen DR isotype (HLA-DR) molecule expression. Combination of bexmarilimab with current standard-of-care (SoC) drugs, azacitidine and venetoclax, showed potential for HLA-DR induction and enhanced killing of leukemic cells, respectively. Our non-clinical findings support the feasibility of CLEVER-1 inhibition in AML/MDS to induce antigen presentating molecule expression and potentially, an anti-leukemic effect together with SoC. Therapeutic targeting of CLEVER-1 with bexmarilimab is currently undergoing clinical investigation in the BEXMAB trial (NCT05428969).